2018
DOI: 10.4317/jced.54368
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of dilaceration in a mexican school-based population

Abstract: BackgroundThe aim of this study was to record the frequency of dilaceration in patients attending our institution and to analyze the possible associated factors.Material and MethodsOrthopantomograms from all patients attended in our institution were reviewed and those cases of dilaceration were selected. Documented data were age, gender, diagnosis, location and involved teeth. Data on possible etiological factors was also recorded.Results125 dilacerated teeth in 99 patients were found. Dilacerations were more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Dilaceration is a well-known DDA involving change in the normal alignment of the root and the crown. Features of this entity are not well understood and present data on its origin, frequency, gender preference and most commonly involved teeth is controversial (4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dilaceration is a well-known DDA involving change in the normal alignment of the root and the crown. Features of this entity are not well understood and present data on its origin, frequency, gender preference and most commonly involved teeth is controversial (4).…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, we reported the frequency of dilacerated teeth in the population attended in our institution (4). During the review of these radiographic material we were able to detect that several cases of dilacerated teeth were associated with other dental developmental alterations (DDAs).…”
Section: Introductionmentioning
confidence: 99%
“…A second theory deals with a developmental disorder of uncertain origin when a traumatic factor wass unknown. 1,3,6 Careful radiography interpretation could detect changes in the normal structure of roots in the mandibular molar. To avoid difficulties or canal loss during root canal therapy, an accurate identification of the third root was required.…”
Section: Discussionmentioning
confidence: 99%
“…Tomes in 1848 was the first to report dilaceration as a seldom seen developmental change of the dental root. [1][2][3] Dilaceration occurs when the development of the tooth is disrupted, resulting in a steep bend or curve in the crown or root. 4 When the mesial or distal tilt of the root is equal to or exceed 90 degrees in regard to the tooth or root axis, Hamasha et al (2002) and Malcic et al (2006) consider the tooth to be dilacerated.…”
mentioning
confidence: 99%
See 1 more Smart Citation